2018
DOI: 10.1111/1365-2664.13189
|View full text |Cite
|
Sign up to set email alerts
|

Predation risk shaped by habitat and landscape complexity in urban environments

Abstract: Habitat loss and modification are hallmarks of anthropogenic ecosystems, but the consequences for ecosystem functioning and service provisioning often remain unclear. Understanding these links in cities is complicated by strong but fine‐scale differences in habitat structure among green space patches, and a high variance in habitat amount across urban landscapes. We used airborne laser scanning data to disentangle the effects of 3D woody habitat heterogeneity of urban home gardens, and woody habitat amount at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 50 publications
(107 reference statements)
1
20
0
Order By: Relevance
“…While above-ground BEF relationships are often shaped by an interaction of local-scale (e.g. vegetation structure ) and landscapescale factors (Angold et al, 2006;Frey et al, 2018a), our understanding of how such multi-scale factors affect the belowground BEF relationships is still limited (Lin and Egerer, 2018). For example, recent studies of ecosystems services rarely addressed the high spatial heterogeneity and complexity of urban soils (Ziter and Turner, 2018), and neither consider the variety of direct and indirect anthropogenic influences across spatial scales (Enloe et al, 2015), nor the role of different aspects of biodiversity (Schwarz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While above-ground BEF relationships are often shaped by an interaction of local-scale (e.g. vegetation structure ) and landscapescale factors (Angold et al, 2006;Frey et al, 2018a), our understanding of how such multi-scale factors affect the belowground BEF relationships is still limited (Lin and Egerer, 2018). For example, recent studies of ecosystems services rarely addressed the high spatial heterogeneity and complexity of urban soils (Ziter and Turner, 2018), and neither consider the variety of direct and indirect anthropogenic influences across spatial scales (Enloe et al, 2015), nor the role of different aspects of biodiversity (Schwarz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We observed an extremely high proportion of attacked caterpillars during the whole experiment: 84.25% in only two days. Studies conducted in different environments, such as tropical savanna, urban area and tropical forest, that left models exposed for over four days observed attack marks on only 11.7, 16.2 and 20.9% of caterpillars, respectively (Moreno & Ferro, 2012;Leles et al, 2017;Frey et al, 2018). Therefore, our study demonstrated that caterpillar models can be used efficiently to explore the relationships between ants, the resources provided by plant species and herbivorous insects.…”
Section: Discussionmentioning
confidence: 52%
“…birds, reptiles or chewing insects) (Low et al, 2014) (Fig 1B). These models have already provided useful information about the effects of plant and vegetation structure (Leles et al, 2017;Frey et al, 2018) and caterpillar characteristics (Hossie & Sherratt, 2012) on the relationships between caterpillars and their natural enemies. Ants have been shown to be responsible for most of the attacks on dummy caterpillars (Roslin et al, 2017), evidence that caterpillar models are efficient tools to assess the ants' response towards herbivorous arthropods (Leles et al, 2017).…”
Section: Experimental Designmentioning
confidence: 99%
“…Since many ecosystem functions ultimately rely on interactions between primary producers (plants) and other trophic levels (e.g. pollinators, soil decomposers, and herbivores), the redundancy and resilience framework (e.g., Elmqvist et al 2003) should be extended to multi-trophic systems (Lavorel et al 2013) and include metrics of biotic interactions (for measuring functional redundancy and response diversity) as indicators of functionally resilient urban ecosystems (e.g., Frey et al 2018;Tresch et al 2019).…”
Section: Provision Of Habitat For Biodiversitymentioning
confidence: 99%